(3fOhI JcQje eMehO cGeds - (3GdeLdS GdCYdi ddKbGaIs ((3GdbGgQIs (3GdeLdS GdCYdi ddKbGaIs, 2001)
(3jJfGhd fOhI JcQje GdehSjbi eMehO cGed ef NdGd YOO ef GdehSjbjhfs
hurg
5 6 8 14 20 22
Keywords: (3ehSjbi GdQhGOs